ANALYSIS OF THE FLIGHT OBJECT CONCEPT - Kharchenko, Volodymyr; Luppo, Oleksandr; Bo, Wang; Argunov, Gennadiy; Vasyliev, Denys; Raksha, Karyna (Proceedings of National Aviation University, 2015)
The article represents an analysis of the Flight Object concept implementation in Europe. The objectives, features and interoperability performances of the Flight Object are considered. The multiobjective model for the efficiency estimation of the Flight Object implementation has been developed. The integral efficiency criterion is defined using the Harrington’s desirability generalized function.